Easier way to apply multiple arguments in Haskell - haskell

Given value f with type :: Applicative f => f (a -> b -> c), What's the best way to map arguments to the inner function.
So far I've found the following:
(\x -> x a b) <$> f
(flip ($ a) b) <$> f
($ b) <$> ($ a) <$> f
I guess my question is why Haskell doesn't have a :: a -> b -> (a -> b -> c) -> c function. Or does it?

The Applicative class has the <*> operator (usually pronounced "ap", and is equivalent to Control.Monad.ap for most Monads), which combined with the <$> operator (itself just an infix alias for fmap) lets you write code like
-- f :: a -> b -> c
-- fa :: Applicative f => f a
-- fb :: Applicative f => f b
f <$> fa <*> fb :: Applicative f => f c
If you need to apply pure arguments, then use the pure method of the Applicative class:
-- f :: a -> b -> c
-- a :: a
-- b :: b
f <$> pure a <*> pure b :: Applicative f => f c
An example might be
sumOfSquares :: Num a => a -> a -> a
sumOfSquares a b = a * a + b * b
> sumOfSquares <$> Just 1 <*> Just 2
Just 5
> sumOfSquares <$> Just 1 <*> Nothing
Nothing
> sumOfSquares <$> pure 1 <*> pure 2 :: Maybe Int
5
> sumOfSquares <$> readLn <*> readLn :: IO Int
1<ENTER>
2<ENTER>
5
The Applicative f => f (a -> b -> c) is being constructed by f <$> here, so if you already had something like
> let g :: IO (Int -> Int -> Int); g = undefined
Then you could just use it as
> g <*> pure 1 <*> pure 2
The <*> operator has the type
(<*>) :: Applicative f => f (a -> b) -> f a -> f b
so if your function has type x -> y -> z, then a ~ x and b ~ y -> z, so repeated application of <*> (get it?) passes more arguments to your wrapped function.

We've got
(<$>) :: Functor f => (a -> b) -> f a -> f b
But you want the opposite
(>$<) :: Functor f => f (a -> b) -> a -> f b
Which we can easily define:
(>$<) f a = ($a) <$> f
So given
f :: Functor f => f (a -> b -> c)
a :: a
b :: b
Then
f >$< a :: f (b -> c)
f >$< a >$< b :: f c
This isn't as idiomatic as <*>, but it works for all Functors, not just Applicatives, which is nice.

Related

Shouldn't fmap (+3) (*3) be equivalent to \x -> ((x+3)*3)?

In Learn you a Haskell, it is given that
fmap (+3) (*3)
is equivalent to
\x -> ((x*3)+3))
However, I can't understand why. Isn't it supposed to be \x -> ((x+3)*3)?
I don't know the implementation of fmap for (*3) functor, but my intuition tells me that since the functor (*3) is equivalent to \x -> x * 3, the map (+3) would be first applied and then (*3) be applied, but it is the other way around. What am I missing in here?
my intuition tells me that since the functor (*3) is equivalent to \x -> x * 3
Functions form a functor instance
instance Functor ((->) r) where ...
Those are the functions mapping from r.
Given a function g :: r -> a you can form a new function h :: r -> b with the help of f :: a -> b via h = fmap f g. It should now be clear that f :: a -> b cannot be applied first but must be applied second. That is h' = (g :: r -> a) . (f :: a -> b) does not make any sense but h = (f :: a -> b) . (g :: r -> a) does.
fmap has to obey two laws:
fmap id == id
fmap (f . g) == fmap f . fmap g
Your proposed definition, fmap' f g == g . f, satisfies the first law but violates the second law:
fmap' id f == f . id == f == id f -- OK
fmap' (f . g) h == h . (f . g)
== (h . f) . g
== (fmap' f h) . g
== fmap' g (fmap' f h)
== (fmap' g . fmap' f) h -- violation, since (.) is not commutative
The correct definition, fmap f g = f . h, satisfies both:
fmap id f == id . f == f == id f
fmap (f . g) h == (f . g) . h
== f . (g . h)
== fmap f (g . h)
== fmap f (fmap g h)
== (fmap f . fmap g) h
A "functor", in Haskell, is a higher order type, F, -- "higher order" meaning, it accepts another type variable, a (denoting any type whatever), -- such that we can have
F a fa
(a -> b) ab
-----------------
F b fmap ab fa
which is known as "flip fmap" (flip just means that the order of arguments is flipped, flip fmap fa ab == fmap ab fa). There are also some "common sense" laws it must follow.
For F ~ Maybe, say, it means
flip fmap :: Maybe a ->
(a -> b) ->
Maybe b
and for F ~ [],
flip fmap :: [] a ->
(a -> b) ->
[] b
which is more conventionally written as [a] -> (a -> b) -> [b].
In our case here, F a ~ r -> a, or more formally, F a ~ ((->) r) a, which means F ~ ((->) r),
flip fmap :: ((->) r) a ->
(a -> b) ->
((->) r) b
which is more conventionally written as (r -> a) -> (a -> b) -> (r -> b),
r -> a
a -> b
-------------
r -> b
which is the same as (r -> a) -> (a -> b) -> r -> b since with types, the arrows associate on the right, corresponding to the fact that applications associate on the left: f a b c is actually ((f a) b) c and
f a b c = d -- f a b c
f a b = \c -> d -- (f a b) c
f a = \b c -> d -- ((f a) b) c
f = \a b c -> d -- (((f) a) b) c
are all different ways to write down the same definition, and different ways to write down the same function call.
This then means we need to implement
fmap :: (a -> b) -> (r -> a) -> (r -> b)
fmap ab ra r = b
where
b =
So what could the definition be? Is it up to us to decode what goes where? Well, we must produce a b type value. The only thing we have that can do it for us, is ab :: a -> b.
Can we produce a b without it? Out of the blue? Except for erroring out, no, we can't -- we know nothing about that b type. It can be anything. So we're left with
b = ab a
a =
and now we must get an a somewhere, to use it as an argument to ab. Fortunately, ra can give it to us:
a = ra r
and r, we already got! So the types did write this implementation for us:
fmap :: (a -> b) -> (r -> a) -> (r -> b)
fmap ab ra r = b
where
b = ab a
a = ra r
or, simplifying and renaming, we get
fmap f g r = f ( g r)
= (f . g) r
by definition of the function composition, ., as
(.) :: (a -> b) -> (r -> a) -> (r -> b)
(f . g) r = f (g r)
which is a valid syntax definition, otherwise written as
(.) :: (a -> b) -> (r -> a) -> (r -> b)
(.) f g r = f (g r)
or
(.) :: (a -> b) -> (r -> a) -> (r -> b)
(.) f g = \ r -> f (g r)
or
(.) :: (a -> b) -> (r -> a) -> (r -> b)
(.) = \f g r -> f (g r)
All these are equivalent. And its type diagram
a -> b
r -> a
--------------
r -> b
As for the intuition, a functorial type value of type F A is, loosely, an F-type "something" than can somehow produce an A-type something, in some F-type sense.
The functor laws mean that F does so in some purely "structural", mechanical way, without regard to what that A value that it produces actually is. In other words, the A values do not influence how they are produced, only the F type itself determines that.
For example, Maybe Int could Maybe produce an Int. Or [Int] could produce several Ints. (*3) can also produce an Int, if we supply it with an Int argument.
What then this fmap is? What does it do? It transforms that would-be produced value. Every functor type must define its fmap, that is what makes it be a functorial type, that it defines the
instance Functor Maybe where
fmap ab (Just a) = (Just (ab a))
etc. So then, with functions r -> a, which produce that a type value promised by their type, after being applied to an argument, we transform that value by applying the transformation function to it:
fmap transf mult3 arg = tansf (mult3 arg)
which is just the definition of the functional composition itself, with arguments renamed.
So that's why, in this case,
fmap (+3) (*3) r = (+3) ((*3) r)
= (+3) (r*3)
= (r*3) + 3
we (+3) transform the value produced by (*3) in the ((->) r) sense, which is application to some user-supplied argument, r. So (*3) must be applied first, to get (it to produce) that value.

In applicative, how can `<*>` be represented in terms of `fmap_i, i=0,1,2,...`?

Class Applicative is declared as:
class Functor f => Applicative f where
pure :: a -> f a
(<*>) :: f (a -> b) -> f a -> f b
We can represent fmapi, i=0,1,2,... in terms of pure and (<*>):
fmap0 :: a -> f a
fmap0 = pure
fmap1 :: (a -> b) -> f a -> f b
fmap1 g x = pure g <*> x
fmap2 :: (a -> b -> c) -> f a -> f b -> f c
fmap2 g x y = pure g <*> x <*> y
fmap3 :: (a -> b -> c -> d) -> f a -> f b -> f c -> f d
fmap3 g x y z = pure g <*> x <*> y <*> z
In applicative, how can <*> be represented in terms of fmap_i, i=0,1,2,...?
Thanks.
See also Is the implementation of `<*>` based on `fmap` special to Maybe applicative or can it be generalized to other applicatives?
You can write:
(<*>) = fmap2 ($)
or, if you find it less obscure:
f <*> a = fmap2 apply f a
where apply g x = g x

Haskell function using Applicative and Functor

I have a practice question, where I'm given a function:
sequence :: Applicative f => [f a] -> f[a]
sequence = foldr (_hole (:)) (pure [])
and the question says:
"What type is required for the function that needs to be placed at
_hole in the following expression? Also give a definition for the
expression using and <$> and <*>".
I'm having issue understanding what the question is asking. So for what I've tried, i assume that I'm required to specify the operator since it's using foldr so i assume its something like sequence = foldr((+) (:)) (pure[]).
Then for the definition of the expression, i wrote something like:
sequence :: <*> f => [f a] -> f[a]
sequence = foldr <$> pure []
I'm pretty sure I'm not 100% correct so would appreciate some help on this on any corrections.
The exercise wants you to assume that some value _hole is defined somewhere, and that the code above type checks. Then, the goal is to determine what would be the type of that _hole. Then, it would ask a possible definition for _hole.
For instance, if we were given
foo :: Int
foo = 3 + _hole
the answer should be _hole :: Int, since that's what we need to make the code above to work. For the definition _hole = 2 is OK.
Instead, in
foo :: Int -> Bool
foo = const _hole "hello" True
then we need _hole :: Bool -> Int -> Bool and for instance _hole = \b i -> b.
Your own code is more complex, so it's better to write down all the steps:
sequence :: Applicative f => [f a] -> f[a]
sequence = foldr (_hole (:)) (pure [])
Here foldr is used, which (on lists) has type
foldr :: (b -> c -> c) -> c -> [b] -> c
To type check, the arguments must have type
_hole (:) :: b -> c -> c
pure [] :: c
the result of foldr, being called with only two arguments is
sequence :: [b] -> c
since this must match the type of sequence above, we get
[b] = [f a]
c = f [a]
Hence, b = f a and
_hole (:) :: f a -> f [a] -> f [a]
pure [] :: f [a]
The pure [] part type checks as it is. For the other, we need
_hole :: (type of (:)) -> f a -> f [a] -> f [a]
i.e. since (:) :: d -> [d] -> [d] for any d, we get
_hole :: (d -> [d] -> [d]) -> f a -> f [a] -> f [a]
where d can be picked arbitrarily. It is "natural", though, to pick d=a, so that we get
_hole :: (a -> [a] -> [a]) -> f a -> f [a] -> f [a]
Now, we need to write a definition _hole f x y = ?? in terms of <$> and <*>. Essentially, we need to re-implement liftA2 from the library. You should now be able to solve this last part.
Let's do it step by step, gradually discovering the types of the entities involved in our definition. We are given
sequence :: Applicative f => [f a] -> f [a] -- (1)
sequence = foldr (_hole (:)) (pure []) -- (2)
so that sequence = mksequence g for some g:
mksequence g xs = foldr (g (:)) (pure []) xs -- (3)
mksequence g [a,b,...,n] = r where -- (4)
r = g (:) a $ g (:) b $ ... $ g (:) n (pure []) -- (5)
mksequence g [a] = g (:) a (pure []) -- (6)
mksequence g [] = pure [] -- (7)
-- [a,b,...,n] :: [f a] <-(4,1) -- (8)
-- a,b,...,n :: f a <-(8) -- (9)
-- r :: f [a] <-(4,1) -- (10)
-- pure [] :: f [a] <-(7,1) -- (11)
-- g (:) :: f a -> f [a] -> f [a] <-(6,8,11,1)
Finally, we've found the type of g (:)! Compare it with
(<*>) :: f (a -> t) -> f a -> f t , _A :: f (a -> t)
(_A <*> _C) :: f t , _C :: f a
(_B <*> _C) :: f (t -> s) , _B :: f (a -> (t -> s))
((_B <*> _C) <*> _D) :: f s , _D :: f t
So that we have,
\ _B _C _D -> ((_B <*> _C) <*> _D)
:: f (a -> (t -> s)) -> f a -> f t -> f s
g ((:) :: a -> [a] -> [a]) :: f a -> f [a] -> f [a]
The signatures nearly match! With just a little nudge we have
g (:) = (\ _B _C _D -> ((_B <*> _C) <*> _D)) (pure (:))
and so, generalizing,
g f2 fa ft = pure f2 <*> fa <*> ft
because (<*>) associates to the left. Re-checking the types,
g f2 fa ft = pure f2 <*> fa <*> ft
= f2 <$> fa <*> ft
-- fa :: f a
-- f2 :: a -> t -> s
-- f2 <$> fa :: f (t -> s)
-- ft :: f t
-- (f2 <$> fa) <*> ft :: f s
In fact this definition already exists, and is named liftA2 -- for "lifting" a binary function (f2) into an applicative "context" (f):
f2 :: a -> t -> s
liftA2 f2 :: f a -> f t -> f s

How does <*> derived from pure and (>>=)?

class Applicative f => Monad f where
return :: a -> f a
(>>=) :: f a -> (a -> f b) -> f b
(<*>) can be derived from pure and (>>=):
fs <*> as =
fs >>= (\f -> as >>= (\a -> pure (f a)))
For the line
fs >>= (\f -> as >>= (\a -> pure (f a)))
I am confused by the usage of >>=. I think it takes a functor f a and a function, then return another functor f b. But in this expression, I feel lost.
Lets start with the type we're implementing:
(<*>) :: Monad f => f (a -> b) -> f a -> f b
(The normal type of <*> of course has an Applicative constraint, but here we're trying to use Monad to implement Applicative)
So in fs <*> as = _, fs is an "f of functions" (f (a -> b)), and as is an "f of as".
We'll start by binding fs:
(<*>) :: Monad f => f ( a -> b) -> f a -> f b
fs <*> as
= fs >>= _
If you actually compile that, GHC will tell us what type the hole (_) has:
foo.hs:4:12: warning: [-Wtyped-holes]
• Found hole: _ :: (a -> b) -> f b
Where: ‘a’, ‘f’, ‘b’ are rigid type variables bound by
the type signature for:
(Main.<*>) :: forall (f :: * -> *) a b.
Monad f =>
f (a -> b) -> f a -> f b
at foo.hs:2:1-45
That makes sense. Monad's >>= takes an f a on the left and a function a -> f b on the right, so by binding an f (a -> b) on the left the function on the right gets to receive an (a -> b) function "extracted" from fs. And provided we can write a function that can use that to return an f b, then the whole bind expression will return the f b we need to meet the type signature for <*>.
So it'll look like:
(<*>) :: Monad f => f ( a -> b) -> f a -> f b
fs <*> as
= fs >>= (\f -> _)
What can we do there? We've got f :: a -> b, and we've still got as :: f a, and we need to make an f b. If you're used to Functor that's obvious; just fmap f as. Monad implies Functor, so this does in fact work:
(<*>) :: Monad f => f ( a -> b) -> f a -> f b
fs <*> as
= fs >>= (\f -> fmap f as)
It's also, I think, a much easier way to understand the way Applicative can be implemented generically using the facilities from Monad.
So why is your example written using another >>= and pure instead of just fmap? It's kind of harkening back to the days when Monad did not have Applicative and Functor as superclasses. Monad always "morally" implied both of these (since you can implement Applicative and Functor using only the features of Monad), but Haskell didn't always require there to be these instances, which leads to books, tutorials, blog posts, etc explaining how to implement these using only Monad. The example line given is simply inlining the definition of fmap in terms of >>= and pure (return)1.
I'll continue to unpack as if we didn't have fmap, so that it leads to the version you're confused by.
If we're not going to use fmap to combine f :: a -> b and as :: f a, then we'll need to bind as so that we have an expression of type a to apply f to:
(<*>) :: Monad f => f ( a -> b) -> f a -> f b
fs <*> as
= fs >>= (\f -> as >>= (\a -> _))
Inside that hole we need to make an f b, and we have f :: a -> b and a :: a. f a gives us a b, so we'll need to call pure to turn that into an f b:
(<*>) :: Monad f => f ( a -> b) -> f a -> f b
fs <*> as
= fs >>= (\f -> as >>= (\a -> pure (f a)))
So that's what this line is doing.
Binding fs :: f (a -> b) to get access to an f :: a -> b
Inside the function that has access to f it's binding as to get access to a :: a
Inside the function that has access to a (which is still inside the function that has access to f as well), call f a to make a b, and call pure on the result to make it an f b
1 You can implement fmap using >>= and pure as fmap f xs = xs >>= (\x -> pure (f x)), which is also fmap f xs = xs >>= pure . f. Hopefully you can see that the inner bind of your example is simply inlining the first version.
Applicative is a Functor. Monad is also a Functor. We can see the "Functorial" values as standing for computations of their "contained" ⁄ produced pure values (like IO a, Maybe a, [] a, etc.), as being the allegories of ⁄ metaphors for the various kinds of computations.
Functors describe ⁄ denote notions ⁄ types of computations, and Functorial values are reified computations which are "run" ⁄ interpreted in a separate step which is thus akin to that famous additional indirection step by adding which, allegedly, any computational problem can be solved.
Both fs and as are your Functorial values, and bind ((>>=), or in do notation <-) "gets" the carried values "in" the functor. Bind though belongs to Monad.
What we can implement in Monad with (using return as just a synonym for pure)
do { f <- fs ; -- fs >>= ( \ f -> -- fs :: F (a -> b) -- f :: a -> b
a <- as ; -- as >>= ( \ a -> -- as :: F a -- a :: a
return (f a) -- return (f a) ) ) -- f a :: b
} -- :: F b
( or, with MonadComprehensions,
[ f a | f <- fs, a <- as ]
), we get from the Applicative's <*> which expresses the same computation combination, but without the full power of Monad. The difference is, with Applicative as is not dependent on the value f there, "produced by" the computation denoted by fs. Monadic Functors allow such dependency, with
[ bar x y | x <- xs, y <- foo x ]
but Applicative Functors forbid it.
With Applicative all the "computations" (like fs or as) must be known "in advance"; with Monad they can be calculated -- purely -- based on the results of the previous "computation steps" (like foo x is doing: for (each) value x that the computation xs will produce, new computation foo x will be (purely) calculated, the computation that will produce (some) y(s) in its turn).
If you want to see how the types are aligned in the >>= expressions, here's your expression with its subexpressions named, so they can be annotated with their types,
exp = fs >>= g -- fs >>=
where g f = xs >>= h -- (\ f -> xs >>=
where h x = return (f x) -- ( \ x -> pure (f x) ) )
x :: a
f :: a -> b
f x :: b
return (f x) :: F b
h :: a -> F b -- (>>=) :: F a -> (a -> F b) -> F b
xs :: F a -- xs h
-- <-----
xs >>= h :: F b
g f :: F b
g :: (a -> b) -> F b -- (>>=) :: F (a->b) -> ((a->b) -> F b) -> F b
fs :: F (a -> b) -- fs g
-- <----------
fs >>= g :: F b
exp :: F b
and the types of the two (>>=) applications fit:
(fs :: F (a -> b)) >>= (g :: (a -> b) -> F b)) :: F b
(xs :: F a ) >>= (h :: (a -> F b)) :: F b
Thus, the overall type is indeed
foo :: F (a -> b) -> F a -> F b
foo fs xs = fs >>= g -- foo = (<*>)
where g f = xs >>= h
where h x = return (f x)
In the end, we can see monadic bind as an implementation of do, and treat the do notation
do {
abstractly, axiomatically, as consisting of the lines of the form
a <- F a ;
b <- F b ;
......
n <- F n ;
return (foo a b .... n)
}
(with a, F b, etc. denoting values of the corresponding types), such that it describes the overall combined computation of the type F t, where foo :: a -> b -> ... -> n -> t. And when none of the <-'s right-hand side's expressions is dependent on no preceding left-hand side's variable, it's not essentially Monadic, but just an Applicative computation that this do block is describing.
Because of the Monad laws it is enough to define the meaning of do blocks with just two <- lines. For Functors, just one <- line is allowed ( fmap f xs = do { x <- xs; return (f x) }).
Thus, Functors/Applicative Functors/Monads are EDSLs, embedded domain-specific languages, because the computation-descriptions are themselves values of our language (those to the right of the arrows in do notation).
Lastly, a types mandala for you:
T a
T (a -> b)
(a -> T b)
-------------------
T (T b)
-------------------
T b
This contains three in one:
F a A a M a
a -> b A (a -> b) a -> M b
-------------- -------------- -----------------
F b A b M b
You can define (<*>) in terms of (>>=) and return because all monads are applicative functors. You can read more about this in the Functor-Applicative-Monad Proposal. In particular, pure = return and (<*>) = ap is the shortest way to achieve an Applicative definition given an existing Monad definition.
See the type signatures for (<*>), ap and (>>=):
(<*>) :: Applicative f => f (a -> b) -> f a -> f b
ap :: Monad m => m (a -> b) -> m a -> m b
(>>=) :: Monad m => m a -> (a -> m b) -> m b
The type signature for (<*>) and ap are nearly equivalent. Since ap is written using do-notation, it is equivalent to some use of (>>=). I'm not sure this helps, but I find the definition of ap readable. Here's a rewrite:
ap m1 m2 = do { x1 <- m1; x2 <- m2; return (x1 x2) }
≡ ap m1 m2 = do
x1 <- m1
x2 <- m2
return (x1 x2)
≡ ap m1 m2 =
m1 >>= \x1 ->
m2 >>= \x2 ->
return (x1 x2)
≡ ap m1 m2 = m1 >>= \x1 -> m2 >>= \x2 -> return (x1 x2)
≡ ap mf ma = mf >>= (\f -> ma >>= (\a -> pure (f a)))
Which is your definition. You could show that this definition upholds the applicative functor laws, since not everything defined in terms of (>>=) and return does that.

Composing Monadic Functions with `<=<`

I'm trying to understand the <=< function:
ghci> :t (<=<)
(<=<) :: Monad m => (b -> m c) -> (a -> m b) -> a -> m c
As I understand it, I give it 2 functions and an a, and then I'll get an m c.
So, why doesn't this example compile?
import Control.Monad
f :: a -> Maybe a
f = \x -> Just x
g :: a -> [a]
g = \x -> [x]
foo :: Monad m => a -> m c
foo x = f <=< g x
For foo 3, I would expect Just 3 as a result.
But I get this error:
File.hs:10:15:
Couldn't match expected type `a0 -> Maybe c0'
with actual type `[a]'
In the return type of a call of `g'
Probable cause: `g' is applied to too many arguments
In the second argument of `(<=<)', namely `g x'
In the expression: f <=< g x Failed, modules loaded: none.
There are two errors here.
First, (<=<) only composes monadic functions if they share the same monad. In other words, you can use it to compose two Maybe functions:
(<=<) :: (b -> Maybe c) -> (a -> Maybe b) -> (a -> Maybe c)
... or two list functions:
(<=<) :: (b -> [c]) -> (a -> [b]) -> (a -> [c])
... but you cannot compose a list function and maybe function this way. The reason for this is that when you have a type signature like this:
(<=<) :: Monad m => (b -> m c) -> (a -> m b) -> (a -> m c)
... the compiler will ensure that all the ms must match.
The second error is that you forgot to parenthesize your composition. What you probably intended was this:
(f <=< g) x
... if you omit the parentheses the compiler interprets it like this:
f <=< (g x)
An easy way to fix your function is just to define a helper function that converts Maybes to lists:
maybeToList :: Maybe a -> [a]
maybeToList Nothing = []
maybeToList (Just a) = [a]
This function actually has the following two nice properties:
maybeToList . return = return
maybeToList . (f <=< g) = (maybeToList . f) <=< (maybeToList . g)
... which are functor laws if you treat (maybeToList .) as analogous to fmap and treat (<=<) as analogous to (.) and return as analogous to id.
Then the solution becomes:
(maybeToList . f <=< g) x
Note that, in
(<=<) :: Monad m => (b -> m c) -> (a -> m b) -> a -> m c
m is static -- You're trying to substitute both [] and Maybe for m in the definition -- that won't type check.
You can use <=< to compose functions of the form a -> m b where m is a single monad. Note that you can use different type arguments though, you don't need to be constrained to the polymorphic a.
Here's an example of using this pattern constrained to the list monad:
f :: Int -> [Int]
f x = [x, x^2]
g :: Int -> [String]
g 0 = []
g x = [show x]
λ> :t g <=< f
g <=< f :: Int -> [String]
λ> g <=< f $ 10
["10","100"]
You can't mix monads together. When you see the signature
(<=<) :: Monad m => (b -> m c) -> (a -> m b) -> a -> m c
The Monad m is only a single Monad, not two different ones. If it were, the signature would be something like
(<=<) :: (Monad m1, Monad m2) => (b -> m2 c) -> (a -> m1 b) -> a -> m2 c
But this is not the case, and in fact would not really be possible in general. You can do something like
f :: Int -> Maybe Int
f 0 = Just 0
f _ = Nothing
g :: Int -> Maybe Int
g x = if even x then Just x else Nothing
h :: Int -> Maybe Int
h = f <=< g

Resources